Deciphering the full spectrum of phonon scattering by point defects - Sun, Yandong; Han, Jian; Zhou, Yanguang; Xu, Ben (Journal of applied physics, 2025)
The change in mass and induced strain effects at the point defect sites lead to phonon scattering, which, in turn, reduces thermal conductivity. The scattering mechanism of phonons typically depends on the relative relationship between the defects and the phonon wavelength. Traditional views suggest that point defects give rise to additional modes with specific frequency, exhibiting fixed scattering patterns. However, experimental results in real materials reveal controversy and a range of scattering behaviors, suggesting that the interaction between phonons and point defects varies with wavelength. This phenomenon has yet to be systematically studied. This study introduces a novel approach using spectral energy density based on molecular dynamics simulations to explore the scattering behavior of phonons of different wavelengths by point defects in large-scale material systems. We found that multiple scattering patterns coexist in the phonon scattering behavior of point defects, with different phonon frequencies showing varying frequency-dependent scattering rates. We provided profound insights into the design of materials with tailored thermal conductivities, highlighting the significant role of point defects in modulating thermal transport properties.